Behavioral Oscillations in Visual Attention Modulated by Task Difficulty - Chen, Airui; Wang, Aijun; Wang, Tianqi; Tang, Xiaoyu; Zhang, Ming (Frontiers in Psychology, 2017)
The spotlight of attention is full of discrete moments and operates periodically. Recently, it has been well-documented there were behavioral oscillations in visual attention, however, different periodicities were demonstrated. Task difficulty may be an important factor causing disagreement in attentional periodic patterns. The present study examined behavioral oscillations in visual attention during difficult and easy tasks. A modified high temporal resolution cue-target paradigm in which the cue-target stimulus onset asynchrony (SOAs) varied from 0.1 to 1.08 s in steps of 20 ms was used. The target was detected with the accuracy of 65% in the difficult condition and 75% in the easy condition. Oscillatory patterns were analyzed and observed in behavioral performance. A theta rhythm was visible in the difficult version. However, attention oscillation increased to a higher frequency in the easy version. Task difficulty was negatively related to power for all bands. Our findings suggest that the attention spotlight switched faster when the task was easy, while, it switched much more slowly when the task was difficult in order to obtain more information. A flexible mechanism for attention spotlight was demonstrated, and task demand modulated attention oscillations.